2015
DOI: 10.1177/0143831x15609117
|View full text |Cite
|
Sign up to set email alerts
|

Crisis-related collective bargaining and its effects on different contractual groups of workers in German and Belgian workplaces

Abstract: This article investigates the effects of crisis-related collective bargaining on different contractual groups of workers. Comparing four workplaces of two multinationals in Germany and Belgium in the recent economic crisis, the authors observe that Belgian unions could protect some temporary workers' jobs and when the crisis endured, the jobs and working conditions of the permanent workforces. In contrast, temporary jobs in the German workplaces were not protected and later on, the works councils had to conced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…This empirical evidence contributes to the growing industrial relations literature focusing on workplace dualisation and labour strategies (e.g. Doerflinger and Pulignano, ; Pulignano and Keune, ) because it clearly illustrates how the wider context of liberalisation and international competition and local external circumstances affect labour strategies and power resources at workplace during negotiations on dualisation (Holst, ). This account is only partly compatible with the dualisation literature, which attributes a central role to labour preferences and cross‐class coalitions at workplace in the labour market dualisation in Germany (Hassel, ; Palier and Thelen, ).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…This empirical evidence contributes to the growing industrial relations literature focusing on workplace dualisation and labour strategies (e.g. Doerflinger and Pulignano, ; Pulignano and Keune, ) because it clearly illustrates how the wider context of liberalisation and international competition and local external circumstances affect labour strategies and power resources at workplace during negotiations on dualisation (Holst, ). This account is only partly compatible with the dualisation literature, which attributes a central role to labour preferences and cross‐class coalitions at workplace in the labour market dualisation in Germany (Hassel, ; Palier and Thelen, ).…”
Section: Discussionmentioning
confidence: 57%
“…This article demonstrates the value of incorporating workplace dynamics in national‐level accounts of labour market dualisation, thereby further developing the contribution of the industrial relations literature to political economy debates (e.g. Doerflinger and Pulignano, ; Pulignano and Keune, ).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Even though it was sometimes argued that along with the "decline" of corporatism (e.g., Molina and Rhodes, 2002) the scope and intensity of EBA involvement weakened slightly over time there is evidence that since the advent of the economic crisis in Europe the involvement of EBAs in the public policy making agenda increased significantly again. This, however, includes both bi-and tripartite policy making (e.g., Doerflinger and Pulignano, 2015;Marginson and Galetto, 2016). The bottom line is that, in different countries, different institutional structures and institutions of business and employer interest representations emerged which differ significantly in their degree of "influence".…”
Section: Employer and Business Associations: A Relic Of A Different Era?mentioning
confidence: 99%
“…The literature on collective bargaining in situations in which job losses are likely to occur provides insights into how trade unions can be expected to deal with the emerging jobs-versus-environment dilemma. Ongoing since the 1980s, the debate on concession bargaining has demonstrated that unions have in many instances adopted bargaining strategies aimed at safeguarding employment and improving company competitiveness, even if these strategies contradict general principles upheld by unions such as the defence of working conditions and broader solidarity among workers (Cappelli, 1985; Doerflinger and Pulignano, 2018). Literature dealing with the consequences of the US recession in the 1980s indicates that unions accepted to reduce or freeze wages, cut back benefits, implement two-tier wage plans for new hires and increase overall flexibility to strengthen company competitiveness in exchange for job guarantees, no-layoff policies or earning protection (Cappelli, 1985; Kochan et al, 1986).…”
Section: Climate Change and The Jobs-versus-environment Dilemmamentioning
confidence: 99%